TOWARDS AN AESTHETICS OF SILENCE AND SLOW TIME: TEMPORAL AND SPATIAL TRANSCENDENCE IN THE FILMS OF G. ARAVINDAN - Lalith. S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Cinema as many of the art forms is an intervention, a becoming, a creative enterprise which is godly in its adherence to the creative principle. It etches images and moments by possessing, inhabiting and filling up spaces and time which otherwise would have remained unarchived. It is this idea of intervention in time and space, and the creation of a parallel universe not controlled by the diktats of linearity and narrative, not at all catering to the demands of the market and the conventions of time that distinguishes G. Aravindan. In his films, Aravindan chooses a locale and time removed physically from his own but ever present as part of his consciousness of the human condition. His consciousness in that sense encompasses different terrains and manifold specks of time. He traverses different timescapes and presents them in his inimitable style. This research paper analyses the treatment of temporal and spatial aspects of the films directed by G. Aravindan, and attempts to establish that the characters in his films are ‘always our contemporary’, defying the constraints of time and space. The research paper attempts to place Aravindan in the context of the cinematic traditions that stretches from Ozu and Tarkovsky to the contemporary masters of slow cinema at the same time trying to establish how an Indian way of understanding time also informs his movies.